Bistability of Light Plateaus and Oscillatory States for Counterpropagation in Ring Resonators - Campbell, G. N.; Zhang, S.; Del Bino, L.; Del Haye, P.; Oppo, G. L. (Optics InfoBase Conference Papers, 2022)
Stable light plateaus between two switching fronts are bistable with oscillatory states of homogeneous shape for two input beams counterpropagating in a ring resonator with normal dispersion. The plateaus are not the homogeneous states.
CRIS-Team Scopus Importer:2024-12-16